The Great War: Bachi’s statistic and economic-comparative approach = La Gran Guerra: enfoque estadístico y económico-comparativo de Bachi (Pecvnia : Revista de la Facultad de Ciencias Económicas y Empresariales, Universidad de León, 2016)
Multifaceted intellectual and expert in economics and statistics, Riccardo Bachi was able to understand, in real-time, the long-term implications arising in Italy as a result of involvement in the war. A essential objective of this paper meant to explore some methodological aspects of Bachi’s analysis, i.e. his economic indexes, barometers, thermometers and generally his predictive economic statistics. The comparative statistical method together with the historical-economic approach, make the study of this economist very interesting for the scientific community interested in this historical period, even considering that he developed his research when the statistical sources were not yet available. The last but not the least, the post-war activities of Bachi in commenting on the economic and political consequences of the conflict, would have anticipated, surprisingly, the thought of J.M. Keynes.Multifacético intelectual y experto en economía y estadística, Riccardo Bachi fue capaz de comprender, en tiempo real, las implicaciones a largo plazo que surgen en Italia como resultado de su participación en la guerra. Un objetivo esencial de este trabajo era explorar algunos aspectos metodológicos del análisis de Bachi, es decir, sus índices económicos, barómetros, termómetros y, en general, sus estadísticas económicas predictivas. El método estadístico comparativo, junto con el enfoque histórico-económico, hacen que el estudio de este economista sea muy interesante para la comunidad científica interesada en este período histórico, aun considerando que desarrolló su investigación cuando las fuentes estadísticas aún no estaban disponibles. Por último, pero no menos importante, podemos destacar la actividad de Bachi posterior a la guerra, comentando las consecuencias económicas y políticas del conflicto, con lo que, sorprendentemente, se habría anticipado al pensamiento de J.M. Keynes.